Fluvial adjustments due to straightening and inadequate management of urban drainage: the Maringá Stream catchment, Southern Brazil - Beltramin, Kenia Ketiri; Morais, Eduardo Souza de (Revista Brasileira de Geomorfologia, 2024)
The morphological channel changes can occur through direct interventions, such as engineering works, or indirectly due to alterations in the catchment runoff. This study conducted morphometric evaluations using geoprocessing techniques and fieldwork in fluvial reaches altered by straightening and influenced by urbanization in the Maringá Stream catchment, located in the northern state of Paraná, Brazil. The study analyzed the sinuosity index and the average width of three representative reaches between the years 1970 and 2017. The sinuous morphology of the reaches was straightened in the 1970s and 1980s and did not re-establish itself. Over the past two decades, these reaches exhibited a trend of increasing average width (~100%) due to urbanization in the drainage areas. However, intermittent periods of channel narrowing were also observed. This behavior is associated with bank erosion and failure, leading to the formation of benches. The morphogenesis of this relief unit in the channel results from inadequate management of stormwater runoff from urban areas. This scenario indicates the need for coordinated efforts between urban stormwater management and fluvial geomorphology to maintain the physical integrity of rivers.